Mode I fracture of a soft gel - Lim, Eric Dao Wei (2019)
The Mode I Fracture of a Soft Gel started as an initiative for students to design an experimental set up in order to observe how cracks propagate when subjected to pure bending. In this project, the author was tasked to design and set up methods to allow such study to be made. As this is a total new project and there are no previous experiments conducted to observe how soft materials fail by Mode I Fracture, the design process of the experiment is kept as simple as possible. Before the design process, multiple areas of studies were carried out which include, the usefulness as well as the potential applications of soft materials in the future, the Young’s Modulus of hard and soft materials in order to make a comparison of the results obtained from the specimen used, and the different modes of Fracture Mechanics. After which the ideal methods are identified and designing of the experiment proceeded. The design considers mainly if the specimen subjected to the test is in a pure bending moment. The use of a free body diagram is analysed to ensure that the designed experiment meets the purpose of the carrying out the experiment. After ensuring the design is suitable, materials are then purchased, and the experiment is set up. After a series of experiments, the results are then compiled and a summary is made, completing the project.